Effect of jambu mawar [Syzygium jambos (L.) Alston] leaves extract on natural microbial populations in food - S.K., Ali; R., Son; M.A.R., Nor Khaizura; Y., Rukayadi (Rynnye Lyan Resources, 2022)
Raw food materials can be contaminated with foodborne pathogens and foodborne spoilage. Washing raw food material with water can reduce microbial loading in raw food material prior to the process, but not eliminate it. Due to food safety issues, synthetic food sanitisers are currently being avoided. Natural food sanitisers such as plant extracts are now widely researched and may be used. Jambu mawar [Syzygium jambos (L.) Alston] leaves extract has been reported for its medicinal uses and treatment of a variety of illnesses. The current study aimed to evaluate the effectiveness of jambu mawar leaves extract in order to determine its suitability as a natural food sanitiser. There were three different concentrations (0.05%, 0.50% and 5.00%) of jambu mawar leaves extract solutions used to treat shrimp and cherry tomatoes with immersion method at different exposure times (5 mins and 15 mins). Moreover, the treated samples were stored at different temperatures (25±2oC, 4±2oC, and -18±2oC) for 23 days. The results showed that washing with tap water for 5 mins and 15 mins, was not able to reduce the population of total plate count (TPC), Vibrio parahaemolyticus, Staphylococcus aureus and Klebsiella pneumoniae in food samples. In contrast, washing with 0.05% for 5 mins can significantly reduce the microorganism population in food samples. If the concentration is increased to 5.00% the microbial population in the food samples can be removed completely. Correspondingly, the extract can also inhibit or kill the microbial population in raw food materials at different temperatures. It can be concluded that S. jambos (L.) Alston leaves extract can reduce or eliminate the microbial population in raw food materials. These results suggested that this extract might be developed as a natural food sanitiser.